Expert consensus statement on risk management for scraping treatment (刮痧意外情况处理专家共识) - Beijing Office of Traditional Chinese Medicine Nursing Competence Improvement Project (北京市中医护理能力提升工程办公室，北京市中医技术质控中心) (中西医结合护理)
Scraping therapy has the therapeutic effect of dredging meridians, regulating viscera and eliminating toxins. Because of its many advantages, this therapy has become one of the most widely used external treatment methods of Traditional Chinese Medicine in clinical practice. However, this therapy has strict requirements for the operation of the operator. Once the operation is improper, it may cause accidents. The importance of timely identification and treatment of accidents caused by scraping has been recognized by more and more scholars. Based on this, the Beijing Office of Traditional Chinese Medicine Nursing Competence Improvement Project and the Beijing Traditional Chinese Medicine Nursing Quality Control Center had established a consensus formulation group and expert group. Referring to the relevant national standards and domestic guidelines of scraping, combined with the actual clinical research results, the expert consensus statement was formulated to further standardize and guide the treatment of clinical scraping accidents and promote the further development of scraping technology. (刮痧疗法具有疏通经络、调节脏腑、排除毒素等治疗作用, 因其诸多优点, 该疗法已成为临床应用广泛的中医外治疗法之一。但该疗法对施术者的操作有着严格的要求, 一旦施术不当, 就可能引起意外情况的发生。及时识别、处理由刮痧产生的意外情况的重要性得到越来越多学者的认同。基于此, 北京市中医护理能力提升工程办公室与北京市中医技术质控中心成立共识制定组与专家组, 参考刮痧相关国家标准、国内指南等文献, 结合临床实际调研结果, 制定本专家共识, 以期进一步规范及指导临床刮痧意外情况处理, 推动刮痧技术的进一步发展。)